Polarization tomography of photon pairs emitted by nonlinear metasurfaces with quasi-bound states in the continuum resonances - Noh, Jiho; Santiago-Cruz, Tomás; Gennaro, Sylvain D.; Sultanov, Vitaliy; Brener, Igal; Chekhova, Maria V. (CLEO: Fundamental Science, CLEO:FS 2024 in Proceedings CLEO 2024 - Part of Conference on Lasers and Electro-Optics, 2024)
We use complete polarization tomography of photon pairs generated in semiconductor metasurfaces via spontaneous parametric down-conversion to show how bound states in the continuum resonances affect the polarization state of the emitted photons.
CRIS-Team Scopus Importer:2024-10-25